Reliability, Conformance Dan Perceived Quality Dalam Meningkatkan Kualitas Produk - Erwin Setiawan; Christian Herdinata (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2015)
This research aims to increase the dimensions of reliability, suitability, and the impression of quality in an effort to improve the quality of fish fillet products STB. The object of this research is Sumber Tujuh Berkat company. The subjects of this research are customers, similar companies, experts, and the owner. Using purposive sampling, seven informants chosen by researchers as informants. Primary data are taken based on the results of depth interviews and documentation to the informants. Secondary data is taken from STB’s company data, reference books, journals, and the Internet that can support this research. The data collection techniques used are in depth interview and documentation. In testing the validity of the data, the researcher uses triangulation techniques. The triangulation used is source triangulation. The sources used are customers, similar companies, experts, and STB’s owner. The result of this study is how to improve the quality of fish fillet STB’s products. This improvement was made on the dimensions of reliability, conformance, and the perceived quality of fish fillet STB’s products. The way to do is training the employees regarding the filleting process which is true to the knowledge of experts, STB need to replace old equipment with a fish fillet special equipment, STB need to cooperate to fish breeder so the materials purchased has a uniform size and weight, and STB needs to get permission from BPOM to impress the product quality can be improved in the eyes of consumers.